Логарифмическая асимптотика одного класса отображений - Салимов, Р.Р. (Український математичний вісник, 2018)
В работе исследуется асимптотическое поведение в точке нижних Q-гомеоморфизмов относительно p-модуля в Rⁿ, n ≥ 2. Получен целый ряд логарифмических оценок для нижних пределов при различных условиях на функцию Q. В работе приведены приложения этих результатов к классам Орлича–Соболева W1,φ loc в R≥, n ≥> 3 при условии типа Кальдерона на функцию φ и, в частности, к классам Соболева W1,p loc при p > n -1. Построен пример гомеоморфизма с конечным искажением, показывающий точность найденного порядка роста. The asymptotic behavior of lower Q-homeomorphisms relative to a p-modulus in Rⁿ, n ≥> 2, at a point is studied. A number of logarithmic estimates for the lower limits under various conditions imposed on the function Q are obtained. Some applications of these results to the Orlicz–Sobolev classes W1,φ loc in Rⁿ, n ≥ 3 under the Calderon-type condition imposed on the function φ and, in particular, to the Sobolev classes W1,p loc for p > n − 1 are given. The example of a homeomorphism with finite distortion which shows the exactness of the found order of growth is constructed.